Using The Utaut Model to Understand Social Media's Adoption for Enhancing Academic Performance among Indian University Students. - Manish Kumar, Sandeep Kumar, (European Economic Letters (EEL), 2024)
Leveraging the UTAUT model, this study dissects the multifaceted influences of social media on individual and societal integration for learning and academic performance among Indian university students. Employing a quantitative survey approach, the research assesses how key UTAUT constructs, including performance expectancy, effort expectancy, social influence, facilitating conditions, and perceived playfulness, impact students' adoption of SM for educational purposes and its subsequent effect on academic outcomes. The findings reveal that social and peer influence significantly contribute to positive attitudes toward using SM for learning. However, concerns are raised regarding potential misuse, prompting recommendations for parental or institutional management intervention if necessary. Additionally, the study expands the original UTAUT model by introducing two additional variables: peer pressure and conditions of social media platforms. Results indicate that peer pressure positively influences SM adoption for learning, while specific platform features and functionalities are crucial in determining its effectiveness. Moreover, the study highlights the potential drawbacks of solely using SM for non-academic activities like entertainment and social interactions, which could negatively impact the student experience. This study sheds light on the crucial relationship between social media integration, learning processes, and student success in Indian universities.. It offers vital considerations for educational institutions and policymakers seeking to harness the potential of SM while mitigating potential risks associated with its misuse.